Development of client service as a basis for birth of the electronic commerce system - К. A. Zalihina; Т. N. Sakulyeva (Вестник университета)
The purpose of this study is to study the development of customer service as the basis for the emergence of an e-commerce system. Research objectives: to study the aspects of the origin of customer service, to analyse the development of marketplaces abroad and in Russia, to structure expenses when selling goods through the marketplace. The methodology of marketplaces research is based on a deep and thorough study of the needs and moods of customers. The informatization of modern society makes it necessary to adapt business processes to the needs of the consumer, who, due to various factors of the 21st century, are guided by the Internet space, which does not provide the client with a full range of information about the product through the senses. Accordingly, it is necessary to create a level of service that embodies the consumer’s trust in buying goods online.